Magnetic Non-invasive Auricular Acupuncture During Eye-Exam for Retinopathy of Prematurity in Preterm Infants: A Multicentre Randomized Controlled Trial - Kimberly M. L. Gan; Kimberly M. L. Gan; Ju-Lee Oei; Ju-Lee Oei; Im Quah-Smith; Im Quah-Smith; Azanna A. Kamar; Alexis A. D. Lordudass; Kian D. Liem; Kwee Bee Lindrea; Mary Daly; Nilima Gaunker; et al. (Frontiers Media S.A., 2020)
Background: Eye exam for Retinopathy of prematurity (ROP) is a painful procedure and pharmacological analgesia might be ineffective. We hypothesized that magnetic auricular acupuncture (MAA) compared to placebo will decrease pain during ROP exam in preterm infants.Methods: Multicentre randomized controlled trial conducted in three hospitals (Australia, Canada, and Malaysia). Eligibility: >32 weeks, ROP exam, not sedated, and parental consent. A total of 100 infants were randomized (1:1) to MAA (n = 50) or placebo (n = 50). MAA stickers or placebo were placed on both ears by an unblinded investigator. Pain was assessed using the Premature Infant Pain Profile. Primary analyses were by intention-to-treat. ClinicalTrials.gov:NCT03650621.Findings: The mean (standard deviation, SD) gestation, birthweight, and postnatal age were (MAA 28(3) vs. placebo 28(2) weeks; MAA 1,057(455) vs. placebo 952(273) g; MAA 7(3) vs. placebo 7(3) weeks. Placebo infants had significantly higher PIPP scores during [mean difference 1.6 points (95%CI 0.1-3.1)] and 1 h mean difference 1.5 points (95%CI 0.7-2.2) after the procedure (p < 0.03). Heart rate was lower (173(22) vs. 184(18)/min) and oxygen saturations were higher (93.8(6.2) vs. 91.7(6.1)%, p = 0.05) in MAA infants. No adverse effects.Interpretation: MAA may reduce physiological pain responses during and after ROP exam in preterm infants. Assessment of long-term effects are warranted.Clinical trial registration: www.ClinicalTrials.gov, identifier: NCT03650621.